Asesmen Cepat Kerentanan Bangunan Sekolah Muhammadiyah Terhadap Gempabumi di Kecamatan Kasihan Bantul DIY - Restu Faizah; Muhammad Ibnu Syamsi (Universitas Muhammadiyah Yogyakarta, 2017)
School buildings are included as buildings with risk category IV (SNI 1726: 2012) because it is potentially causing multiple casualties if earthquakes occur during school hours. Therefore the readiness of school buildings to face the earthquakes should be prepared well. First of all, a rapid vulnerability assessment of the existing building under earthquake needs to be conducted. If the buildings are vulnerable then it should be followed by a strength check. This research objective is to assess the vulnerability of Muhammadiyah school buildings which are located in Kasihan sub-district of Bantul Regency, using Rapid Visual Screening FEMA 154-2002. There are 8 buildings, consist of elementary, middle school, and senior high school which are scattered in Tirtonirmolo, Tamantirto and Bangunjiwo, Kasihan, Bantul regency. According to FEMA 154-2002, the observation result finds that 4 schools indicated to have structure vulnerability under earthquake hazard so they need further analysis to know more detail about their strength. While the other 4 buildings do not need further analysis. The results of this study can be used as a recommendation for the Muhammadiyah Basic and Secondary Education Council (Majelis Pendidikan Dasar dan Menengah) to conduct more detailed testing for school buildings that are have vulnerabilites. In addition, this research method also can be extend to school buildings or non-school buildings in other areas.